Quantification of Pore Size and Shape Distributions in Intumescent Coating Chars Using Image Processing and Pore‐Identification Algorithms: Effects of Heating Rate - Etxeberria, Ander Labaien; Dreyer, Jochen A. H.; Robson, James; Kiil, Søren (Fire and materials, 2025)
This study investigates the effect of heating rate on intumescent coating char formation with regard to pore morphology. The morphology was extracted from cross‐sectional images of char samples embedded in an epoxy resin, followed by image processing and a pore‐identification algorithm. We highlight the necessity of establishing a clear definition of what constitutes a pore unit, especially when delineating the boundaries of interconnected pores. Depending on the employed pore‐identification algorithm, the calculated average pore size and shape vary substantially. A refined approach was developed to identify and measure the morphology of these materials. Adopting this methodology facilitated a meaningful mapping of the pore dimensions in intumescent chars while also capturing small details. Elliptical pore regions were identified realistically, avoiding their oversegmentation into excessively small subpores. Results show stratified and heterogeneous structures with the largest pores predominantly in layers close to the heat source (top layer). Decreasing the heating rate led to larger pore sizes in the top char layer, whereas the smaller pores close to the steel substrate further decreased in size. Additionally, a pore shape analysis revealed a predominantly elliptical morphology, underscoring the practicality of our approach for accurately assessing pore characteristics in intumescent coatings. Overall, this study proposes a cost‐effective and reliable method for pore morphology analysis, offering deep insights into intumescent coating char behavior.